„Sieć’’ przyczyn współczesnego terroryzmu – analiza czynników, mechanizmów i modeli - WOJCIECHOWSKI, Sebastian (Przegląd Politologiczny, 2018)
The issue of terrorism is the subject of numerous studies and analyses. They are usually devoted to its individual manifestations, forms or mechanisms and relatively rarely concern the reasons for the presence and escalation of terrorism. What is more, they often focus on indicating the main factors that trigger terrorism while lacking a profound analysis or attempts at the systemization of the sources of terrorism. Another drawback lies in the emotional or even ideological approach to the subject, which obviously limits the scientific merit of such considerations. Considering the reasons for terrorism one needs to ask several key questions. What are the main factors that generate terrorism? Is it possible to indicate one or several dominating deter- minants among the sources of terrorism? How can they be arranged? Do the present typologies of reasons for terrorism take into account the comprehensive range and specific na- ture of this phenomenon? Apart from answering the above questions, the main purpose of this study is to indicate the main reasons for terrorism combined with the author’s attempt to systemize them by means of the interferential model of reasons for terrorism. It encompasses both the sources of terrorism and their mutual relations, the factors that affect terrorism and the mechanisms and changes that occur with respect to these phenomena.